2019
DOI: 10.1111/opn.12268
|View full text |Cite
|
Sign up to set email alerts
|

Shaping attitudes: The association between prior contact with residential aged care and resistance to enter residential aged care

Abstract: Background The ageing population is increasing, and negative attitudes towards older people are all too common and largely overlooked. However, little research has examined how ageist, prejudice, and discrimination, that often occur in healthcare settings, impact the community's perceptions of entering Residential Aged Care (RAC) in the future. In particular, studies have not investigated how contact with RAC influences individuals’ attitudes towards RAC facilities, residents and staff. This study is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…general public) were more prone to target their stigmatizing evaluations at aged care workers. From a psychological perspective, societal groups may be primed to discredit aged care workers due to the media's intense negative focus on the aged care industry and prior negative contact with institutional aged care (Walker, Dissanayaka, Scott, Manchha & Pachana, 2019). Furthermore, the aged care workforce and student population may target their stigmatizing evaluations at low paid work and negative reactions towards working in aged care, respectively because it is more salient to their identity (Quinn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…general public) were more prone to target their stigmatizing evaluations at aged care workers. From a psychological perspective, societal groups may be primed to discredit aged care workers due to the media's intense negative focus on the aged care industry and prior negative contact with institutional aged care (Walker, Dissanayaka, Scott, Manchha & Pachana, 2019). Furthermore, the aged care workforce and student population may target their stigmatizing evaluations at low paid work and negative reactions towards working in aged care, respectively because it is more salient to their identity (Quinn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Os aspectos teóricos e objetivos dos estudos apresentaram como os idosos são vítimas de discriminação em vários contextos socioculturais, resultante de atitudes negativas frente ao envelhecimento e a pessoa idosa, esse cenário favorece o surgimento do ageísmo. Esse tipo de preconceito ocorre de forma recorrente nos serviços de saúde, principalmente nos ambientes de cuidados médicos (Walker et al, 2019). Em comparação com os outros tipos de preconceito o ageísmo é o menos estudado, socialmente aceito, de difícil investigação e camuflado por atitudes pseudo-positivas, em diversões cenários (França, Siqueira-Brito, Valentin, Vasques-Menezes, & Torres, 2017).…”
Section: Discussionunclassified
“…Nessa perspectiva, o cuidado com o paciente idoso deve ser efetuado de forma integrada, acolhendo o idoso em todas as suas singularidades (Veras & Oliveira, 2018). Em contrapartida, o ageísmo é citado como um dos principais desafios enfrentados pela terceira idade na busca por atendimento (Walker, Dissanayaka, Scott, Manchha, & Pachana, 2019). A partir dessa problemática a seguinte questão de pesquisa emergiu: "Como o ageísmo se expressa e é investigado na assistência à saúde do idoso e quais os desfechos apresentados pela literatura?"…”
Section: Introductionunclassified
“…These concerns are reinforced by negative stereotypes and adverse media attention. 11 Older adults who experience anxiety about transitioning to residential aged care fear losing control over the decision-making process, potentially further impacting their declining health. 12 A review of carers' experiences of a relative transitioning to residential aged care reported that they felt under duress to make a decision that may not have aligned with their personal preferences or cultural values, and they felt the need to defend their decision as their own health was impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Negative experiences of residential aged care by a family member or friend can contribute to increased unease or fear of admission to residential care. These concerns are reinforced by negative stereotypes and adverse media attention 11 . Older adults who experience anxiety about transitioning to residential aged care fear losing control over the decision‐making process, potentially further impacting their declining health 12 .…”
Section: Introductionmentioning
confidence: 99%